A Concise Synthetic Strategy Towards the Novel Calcium-dependent Lipopeptide Antibiotic, Malacidin A and Analogues - Kovalenko, Nadiia; Howard, Georgina K.; Swain, Jonathan A.; Hermant, Yann; Cameron, Alan J.; Cook, Gregory M.; Ferguson, Scott A.; Stubbing, Louise A.; Harris, Paul W. R.; Brimble, Margaret A. (Frontiers in Chemistry, 2021)
Malacidin A is a novel calcium-dependent lipopeptide antibiotic with excellent activity against Gram-positive pathogens. Herein, a concise and robust synthetic route towards malacidin A is reported, employing 9-fluorenylmethoxycarbonyl solid-phase peptide synthesis of a linear precursor, including late-stage incorporation of the lipid tail, followed by solution-phase cyclisation. The versatility of this synthetic strategy was further demonstrated by synthesis of a diastereomeric variant of malacidin A and a small library of simplified analogues with variation of the lipid moiety.